Reactive arthritis after COVID-19 vaccination. Issue 9 (2nd September 2021) - An, Qi-jun; Qin, De-an; Pei, Jin-xian
ABSTRACT: The severe acute respiratory syndrome coronavirus 2-induced coronavirus disease 2019 (COVID-19) has had a global spread. Vaccines play an essential role in preventing the spread. However, almost all types of vaccines have been reported to be associated with adverse events. Reactive arthritis (ReA) after vaccination has been reported; however, ReA after COVID-19 vaccination has not been reported. We reported a 23-year-old woman who suffered from an acute ReA on her left knee joint after COVID-19 vaccination and discussed the etiology and preventive strategy. She presented with swollen, painful left knee joint for 18 d. She had been inoculated 0.5 ml CoronaVac vaccine on 0 d and the 14th day with deltoid intramuscular injection. Finally, she was diagnosed as ReA after CoronaVac vaccination and was administered a single intra-articular injection of 1 ml compound betamethasone. The swelling and pain nearly disappeared after 2 d. On 1month follow-up, her condition was normal. ReA after COVID-19 vaccination is rare. The benefits of vaccination far outweigh its potential risks and vaccination should be administered according to the current recommendations. Further attentions should be put to determine which individual is at higher risk for developing autoimmune diseases after COVID-19 vaccination. More versatile and safer vaccines should be explored.